2022
DOI: 10.15359/ree.26-2.28
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Development of Intercultural Competence in Higher Education Through Intercultural Learning Interventions

Abstract: Introduction. This article analyses the impact of an intercultural learning intervention in a Spanish university post-European Higher Education Area implementation. Objective. Our research’s main objective consisted of measuring the development of intercultural competence in the first cohort of a Translation and Intercultural Communication bachelor’s degree in a Spanish university, before and after taking specific courses in intercultural studies and spending a study abroad semester. Methodology. A mixed metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The results of the present study can be compared with some of the previous studies indicating a positive impact on learners' ICC development by interventions of creating intercultural settings for students to interact with people of different cultures. For example, Nevado-Llopis and Sierra-Huedo studied the impact of specific courses and studying abroad on students' ICC development, and they found that the interventions effectively improve students' intercultural competence [1] . Similarly, Tecedor and Vasseur examined the ICC development by the intervention of videoconferencing conversations between second language learners and native speakers, and the findings provided enlightenment in accurately identifying the development process of learners' intercultural competence and planning proper training interventions [11] .…”
Section: Question 2: How Do Participants Perceive Their Street Interv...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the present study can be compared with some of the previous studies indicating a positive impact on learners' ICC development by interventions of creating intercultural settings for students to interact with people of different cultures. For example, Nevado-Llopis and Sierra-Huedo studied the impact of specific courses and studying abroad on students' ICC development, and they found that the interventions effectively improve students' intercultural competence [1] . Similarly, Tecedor and Vasseur examined the ICC development by the intervention of videoconferencing conversations between second language learners and native speakers, and the findings provided enlightenment in accurately identifying the development process of learners' intercultural competence and planning proper training interventions [11] .…”
Section: Question 2: How Do Participants Perceive Their Street Interv...mentioning
confidence: 99%
“…With the development of globalization and internationalization, intercultural communicative competence (ICC) is a fundamental prerequisite in the workplace, and it is also regarded as one of the major skills required for university students [1] . However, the ICC of Chinese EFL (English as a Foreign Language) undergraduates is not as good as expected [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural integration does not happen automatically through contact with multicultural groups, unless the experience is transformed into a learning experience that develops intercultural competence [15][16][17]. Teachers must therefore be trained not only to implement methods such as cooperative learning, but also to understand the processes involved in adaptation to and integration into a different culture, and to transform the learning environment using intercultural interventions if they are to enhance their learners' intercultural competence [18].…”
Section: Intercultural Education and Intercultural Competencesmentioning
confidence: 99%
“…This requires reflecting on your achievements and failures, as well as changing your goals and strategies based on your learning experience. By following these steps, you can develop your skills in specific areas and improve your overall performance and efficiency (Bentué et al, 2018;Sierra-Huedo & Nevado-Llopis, 2022).…”
Section: Competencementioning
confidence: 99%